A dependência química e religiosas comunidades terapêuticas das cidades paulistas Araçatuba e Tatuí - Vauverde, José (Universidade Federal de São Carlos, 2025)
This research aimed to analyze the work carried out by religious therapeutic communities (TCs) located in the municipalities of Araçatuba and Tatuí, in the years 2024 to 2025. We sought to understand the relationship between the activities of these institutions and public policies aimed at treating drug addicts. Specifically, we sought to: a) understand the forms of assistance offered by the State to these institutions, whether through therapeutic protocols, the provision of professionals in the field, or medical supplements; b) sociologically analyze the conceptions of drugs and health imposed by religious therapeutic communities. To conduct this research, we analyzed national protocols on the treatment of drug addicts, as well as internal documents from two selected institutions. The objective of this monograph was to understand the system of isolation and treatment of drug addicts, in addition to investigating how the disciplines and procedures of the internal regimes of these therapeutic communities are applied. The abuse of psychoactive substances can cause serious psychological, family, and social problems. These substances include both illicit drugs—such as cocaine, heroin, and methamphetamine—and legal but equally addictive substances, such as alcohol, tobacco, and prescription medications, such as prescription drugs used to treat anxiety (anxiolytics) and sleep aids (sedatives or sleeping pills), which can cause dependence. These medications include benzodiazepines (such as diazepam and lorazepam), barbiturates, zolpidem, zopiclone, and others. Chemical dependency can affect people of all ages, genders, groups, and social classes, and the signs and symptoms vary depending on the substance and the individual. Religious doctrines offer a moral and ethical framework to help people overcome addiction, while the community can provide emotional and social support. Therapeutic communities are a form of treatment for those struggling with chemical dependency. For this, sociological reflections are of great importance.
Chemical dependency and religious therapeutic communities in the cities of Araçatuba and Tatuí, in the state of São Paulo
Keywords: Dependência química; Comunidade terapêutica; Políticas Públicas; Terapias religiosas; Chemical dependency; Therapeutic community; Public policies; Religious therapies; CIENCIAS HUMANAS::SOCIOLOGIA